Management of the asymptomatic primary in the palliative treatment of metastatic colorectal cancer. - Clements, D; Dhruva Rao, P; Ramanathan, D; Adams, R; Maughan, T; Davies, M (2009)
OBJECTIVE: The management of the asymptomatic primary in stage IV colorectal cancer presents a dilemma. There is an increased morbidity and mortality from surgical resection. Nonresectional management of the primary is associated with the risks of obstruction, perforation or haemorrhage. Our practice in patients with stage IV disease is palliative chemotherapy and symptom control. We reviewed our nonoperatively managed patients with colorectal liver metastases in order to identify the percentage of patients requiring urgent operative interventions for symptoms related to the primary. SUBJECTS/PATIENTS AND METHOD: A retrospective review of all patients treated for stage IV disease at our institution from 2003-2006 was undertaken. Patients were identified from multidisciplinary team (MDT) records. Demographic detail, treatment, and follow-up data were extracted from hospital records. These were analysed with Microsoft Excel. RESULTS: Thirty-seven patients were identified. 26 Male:11 Female. Median age 63 years (range 38-78). The median survival from diagnosis was 14 months. Three (8%) patients developed obstruction whilst having palliative chemotherapy. Two required a defunctioning stoma, and one was treated by means of a stent. There were no similarities between these three patients in terms of age, sex, site or stage of primary, volume of liver metastases, and alkaline phosphatase (ALP) or carcinoembryonic antigen (CEA) levels. CONCLUSION: Of 37 patients initially treated palliatively for stage IV colorectal cancer, 92% required no surgical treatment of their primary. Therefore it is the experience of this MDT that it is acceptable to treat such patients in an expectant manner. It is not possible to predict those patients, likely to require surgical intervention.